Suggested Syllabus of English I for First Semester students of Islamic Education Department at STAI Al-Gazali Soppeng - Susiyanti Susiyanti; Ria Jubhari; Andi Kaharuddin (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This study investigates the needs of English I for first-semester students at the Islamic Education Department and suggests an English I syllabus based on needs analysis for Islamic Education Department at STAI Al-GAzali Soppeng. This study employed a development research design and simple random and purposive sampling data from 50 students, five graduates, two lecturers, and one curriculum coordinator. The instruments for this study were questionnaires and interviews. The data were gathered through questionnaires by implementing Scala-Likert and were descriptively analyzed. The result shows that (1) students’ ability to learn English I is “poor” in pronunciation. (2) Students’ problems are complex in an oral presentation on learning speaking skills, difficult to understand native speakers on learning the listening skills, difficult to guess the core meaning of the text on learning reading skills, and difficult to compose correct sentences on learning writing. (3) Students prioritize learning preference, preferred topic, and learning style. Dialogue is speaking learning preference. The translation is reading learning preferences, learning from the rules of authorship is writing learning preferences, and listening and practising are listening learning preferences. The preferred topic is Islamic education and the discussion on learning style.